Literacy Movement: How does Mathematics Teacher Integrate it into the Learning Process? - Ikhsan Abdul Latif; Dewi Retno Sari S; Riyadi Riyadi (Pancaran Pendidikan, 2018)
The 2013 Curriculum (K13) 2017 Revision required the teachers to facilitate their students to have the willingness to read by integrating literacy movements into the learning process. This study describes how does the Civil Servant Mathematics teacher integrate literacy movement into the learning process. The subject of this study is a Civil Cervant Mathematics teacher at SMAN 1 Wuryantoro, Wonogiri Regency. Based on the observations and interviews, the teacher 1) compiles long story questions to train students’ ability in reading comprehension, 2) provides opportunities for students to borrow books in the library during group discussions, 3) provides opportunities for students to operate their smartphone to search the materials, 4) assigns individual tasks to the students to look for the articles or journals about the materials, and 5) gives motivation about the importance of reading to integrate the literacy movement.